Ecthyma gangrenosum in the periorbital region in a previously healthy immunocompetent woman without bacteremia - Somenath Sarkar; Arnab Kumar Patra; Madhumita Mondal (Indian Dermatology Online Journal, 2016)
Ecthyma gangrenosum (EG) is a cutaneous lesion classically associated with potentially fatal Pseudomonas septicemia in immunocompromised patients. Other bacterial and fungal pathogens have also been implicated. Although EG typically occurs in immunocompromised or neutropenic patients, it may occasionally affect a previously healthy person. The cutaneous findings are characteristic with small indurated papulovesicles progressing rapidly to necrotic ulcers with surrounding erythema and a central black Eschar. While lesions can occur at any site, most are commonly found over the buttocks, perineum, limbs, and axillae. We describe a case of EG in periorbital region in a previously healthy woman who responded to appropriate antibiotic treatment for Pseudomonas. It is very important to establish the diagnosis early so that appropriate systemic antibiotic therapy can be initiated to reduce morbidity and potential mortality.